Consumer Trust Mediates Live Streaming Optimization and Product Specialization in Increasing Marketplace Purchase Interest - Abdul Salam; Nasharuddin Mas; Survival; Aji Suraji; Rahayu Puji Suci (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study addressed the empirical gap regarding the mechanisms underlying consumer purchase decisions within the direct digital commerce framework, focusing on Erlimakids consumers on Shopee and TikTok Shop. The primary objective was to investigate the structural path of live streaming perceptions and product specialization in driving purchase intentions, while concurrently examining the specific role of marketplace consumer trust as an operational mediator. Utilizing an explanatory quantitative approach based on the Stimulus-Organism-Response model, primary data from 161 validated respondents were statistically analyzed via Structural Equation Modeling Partial Least Squares (SEM-PLS). The structural model evaluation demonstrated that both live streaming quality and strategic product specialization substantially reinforced consumer trust, which subsequently exerted a critical directive influence on purchase intention. Furthermore, product specialization emerged as the most dominant direct determinant of purchase preferences. The mediation analysis verified that consumer trust in the marketplace operated as a substantive partial mediator, indicating a dual-track cognitive mechanism where purchase intention was simultaneously shaped by trust-based psychological evaluations and direct attribute assessment. Consequently, integrating specialized product positioning with interactive digital communication effectively maximized transactional conversions.